Physical activity trend during COVID-19 movement restriction order among UiTM students / Kalam Azad Isa ... [et al.] - Isa, Kalam Azad; Mohd Irwan, Nur Liyana; Mohamed Kasim, Nur Atikah; Ab Razak, Rozella; Mohd Sidi, M. Adli (Universiti Teknologi MARA, 2023)
The government of Malaysia has implemented a Movement Restriction Order (MCO) curfew on all citizens to prevent the Covid-19 pandemic from spreading. Studies have suggested that a long period of MCO will decrease overall weekly spending on energy for physical exercise in all age groups, ultimately promoting hypokinetic diseases. This study is interested in identifying the trend of physical activity behaviour changes during the Covid-19 MCO among university students. This study is also interested in comparing the mean score of physical activity level (inactive, minimum active, sufficient level) among samples. One hundred sixty-five (n=165) healthy samples age 19 to 23 years old currently enrolled as students from the Faculty of Sports Science and Recreation, University Teknologi Mara (FSR) answered the international physical activity questionnaire short form (IPAQ-SF) during the MCO period. Self-Reported Physical Activity Level has shown entirely contradicted from previous studies. 78.2% were at a sufficient level of physical activity; meanwhile, 20% were minimum, and 1.8% were reportedly inactive during the MCO period among FSR students. In addition, this study also found the differences of mean score in physical activity for sufficient level was (1438.78 SE=314.83), minimum active (-1268.65 SE=942.55), and inactive (-2707.43 SE=973.21). This study result showed that although, in restriction conditions in MCO, samples were still able to maintain their physical activity behaviour. The past physical activity practice can explain this phenomenon by these samples required throughout the lesson course, which has become a behaviour among these students.